2010
DOI: 10.2190/pm.40.4.a
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Analysis of Diagnosis of Attention-Deficit/Hyperactivity Disorder in Children: Eastern Wisconsin, USA

Abstract: Further studies are needed to determine if geographic distribution of ADHD diagnosis can be partially explained by differential efficiency of referral for diagnosis by school districts, by race/ethnicity, and/or built environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
(54 reference statements)
3
17
0
Order By: Relevance
“…Another important finding in our study is that children who resided in less urbanized areas were less likely to have ADHD in later life. The geographic effect on the prevalence of ADHD was inconsistent in previous studies (Baumgardner et al., ; Cayce et al., ; Erol et al., ; Gau et al., ; Huss et al., ; Pillai et al., ; Scahill & Schwab‐Stone, ; Zahner et al., ). Pillai et al.…”
Section: Discussionmentioning
confidence: 91%
“…Another important finding in our study is that children who resided in less urbanized areas were less likely to have ADHD in later life. The geographic effect on the prevalence of ADHD was inconsistent in previous studies (Baumgardner et al., ; Cayce et al., ; Erol et al., ; Gau et al., ; Huss et al., ; Pillai et al., ; Scahill & Schwab‐Stone, ; Zahner et al., ). Pillai et al.…”
Section: Discussionmentioning
confidence: 91%
“…For example, geographic studies have linked higher prevalence of ADHD with living at lower altitudes (10) and living in areas with lower solar intensity (11). At a community level, ADHD risk was found to be higher among children living further from a park in Milwaukee County, Wisconsin, suggesting that the built environment may partially explain the uneven geographic distribution of ADHD (12). In Cape Cod, Massachusetts, a community to the east of New Bedford, Hoffman et al (13) observed decreasing odds of ADHD from north to south after adjusting for known risk factors.…”
mentioning
confidence: 99%
“…Despite the polarisation of opinion regarding the prescribing patterns over time, little or no attention has been paid to the diagnosis and treatment of the condition in children with different racial and ethnic backgrounds in Australia. In the US, the occurrence and treatment of the condition has been found to vary with insurance status, 11 family structure 12 and geographic and demographic factors, 13 yet we know little about the possibility of such variations in Australia, where there is stronger policy support for universal access to healthcare.…”
mentioning
confidence: 99%